Verificação do atendimento das recomendações do mapeamento de riscos a inundações no município de Sorocaba - SP - Arruda, Marcia Magalhães de (2016)
This case study presents the profile of the neighborhoods Jardim Abaeté, Parque Vitória Régia, and Parque São Bento, which are classified as medium-risk (R2) and high-risk (R3) flood areas in the North Zone of Sorocaba. The main objective of the research is to assess the management of natural risks based on the guidelines proposed in the Summary of the Risk Mapping Results of the Municipality of Sorocaba, an annex to the Risk Area Mapping for Landslides and Floods prepared by the Geological Institute in 2015. Through the hypothetical-deductive method, bibliographic and documentary research, and the use of the software Google Earth and ArcGIS, an analysis was conducted on the urbanization process and its socio-environmental impacts, with an emphasis on the concepts of risk and vulnerability, examining the adoption of structural and non-structural measures by public authorities aimed at preventing natural disasters. It was evident that measures have been implemented to mitigate the population's risk, with highlights including the construction of a retention basin in Jardim Abaeté, the installation of dikes in Parque Vitória Régia, the relocation of families from risk areas in Parque São Bento, and the installation of a data collection platform (DCP) that monitors the water level of the Sorocaba River and the municipality's rainfall index. The research indicates that the lack of dredging of the Sorocaba River for several years; inadequate urban drainage planning; real estate speculation on land; irregular occupation of floodplains; absence of riparian vegetation in certain areas; high average precipitation levels; and the characteristics of the local terrain are the main factors causing Sorocaba and its neighborhoods to still suffer from flooding during the rainy season, especially in the summer period.